2004
DOI: 10.1016/j.femsec.2004.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Picoeukaryotic diversity in an oligotrophic coastal site studied by molecular and culturing approaches

Abstract: Planktonic picoeukaryotes are important players in coastal marine food webs but little is known about their diversity. Here we report the picoeukaryotic diversity in Blanes Bay (NW Mediterranean) by retrieving environmental 18S rDNA sequences and by obtaining stable cultures. Four genetic libraries (one per season) were constructed and 383 clones analyzed, yielding 176 distinct sequences. The diversity of picoeukaryotes was very large, both at higher and lower phylogenetic levels. Novel alveolates‐I (36% of cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
197
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 209 publications
(204 citation statements)
references
References 46 publications
6
197
1
Order By: Relevance
“…The nonparametric richness estimators have been used in diversity studies of picoeukaryotes/protists only recently (Massana et al, 2004;Zuendorf et al, 2006;Countway et al, 2007). Using a 95% phylotype cutoff, Countway et al (2007) for protistan diversity in a polluted estuary site off the coast of Massachusetts.…”
Section: Diversity Of the Picoeukaryotic Assemblagesmentioning
confidence: 99%
See 1 more Smart Citation
“…The nonparametric richness estimators have been used in diversity studies of picoeukaryotes/protists only recently (Massana et al, 2004;Zuendorf et al, 2006;Countway et al, 2007). Using a 95% phylotype cutoff, Countway et al (2007) for protistan diversity in a polluted estuary site off the coast of Massachusetts.…”
Section: Diversity Of the Picoeukaryotic Assemblagesmentioning
confidence: 99%
“…Using a 95% phylotype cutoff, Countway et al (2007) for protistan diversity in a polluted estuary site off the coast of Massachusetts. For picoeukaryotic diversity, Massana et al (2004) reported one of the highest Chao1 estimates of nearly 200 in an oligotrophic coastal site at Blanes Bay by grouping clones sharing the same RFLP patterns as unique OTUs. In this study, the calculated ACE and Chao1 estimates for picoeukaryotic diversity in subtropical coastal waters ranged from B700 in the TH sample at a cluster distance of 0.10 to B6600 in the MB sample at a cluster distance of 0.02.…”
Section: Diversity Of the Picoeukaryotic Assemblagesmentioning
confidence: 99%
“…For instance, within the heterokonts or stramenopiles, thirteen undescribed clades initially detected in marine surface waters have been reported, i.e. the so-called MAST groups (Massana et al 2004;Massana and Pedrós-Alió 2008). Alveolate sequences from environmental Groups I and II, which are highly abundant in marine clone libraries (Epstein and López-García 2008;Guillou et al 2008), have only recently had their taxonomic identification recognised as Syndiniales.…”
Section: Introductionmentioning
confidence: 99%
“…The 18 S Smallest predators of the oceans J del Campo et al Smallest predators of the oceans J del Campo et al rDNA sequence of our isolate was highly similar to environmental sequences retrieved from the Mediterranean Sea (BL000921.31 and BL010625. 12; Massana et al, 2004), the Sargasso Sea (SSRPE06; Not et al, 2007), and the English Channel (RA070625T.047; Marie et al, 2010). Therefore, we decided to focus in the rhizarian isolate for the rest of our study, given its taxonomic novelty and its similarity with environmental marine sequences.…”
Section: Resultsmentioning
confidence: 99%
“…It is estimated that as little as 0.1% to 1% of bacterial and protist cells can be easily cultured (Caron et al, 1989;Amann et al, 1995). Unfortunately, some of the most highly represented taxa in the environment have not been cultured yet and some of those in culture do not appear to be among the most abundant (Massana et al, 2004;Sherr et al, 2007). Consequently, ultrastructural, physiological and genomic information for many ecologically relevant microorganisms is missing.…”
Section: Introductionmentioning
confidence: 99%